Investigating the Protective Role of Mastery Imagery Ability in Buffering Debilitative Stress Responses - Quinton, Mary Louise; Veldhuijzen van Zanten, Jet; Trotman, Gavin P.; Cumming, Jennifer; Williams, Sarah Elizabeth (Frontiers in Psychology, 2019)
Mastery imagery has been shown to be associated with more positive cognitive and emotional responses to stress, but research is yet to investigate the influence of mastery imagery ability on imagery’s effectiveness in regulating responses to acute stress, such as competition. Furthermore, little research has examined imagery’s effectiveness in response to actual competition. This study examined (a), whether mastery imagery ability was associated with stress response changes to a competitive stress task, a car racing computer game, following an imagery intervention, and (b), the effects of different guided imagery content on pre-task cognitive and emotional responses. In Session 1, 78 participants (M age = 20.03 years, SD = 1.28) completed ratings of pre-task anxiety intensity and direction, confidence, and perceived control. Imagery ability was also assessed before completing the task. In Session 2, participants were randomly allocated to an imagery condition (positive mastery, negative mastery, relaxation) or control group (no imagery) before completing the task and outcome measures again. For the negative mastery group, greater positive mastery imagery ability was associated with greater perceived control and perceiving anxiety as more facilitative. Furthermore, mastery imagery ability moderated the relationship between anxiety intensity and direction. Altogether, results suggest that positive mastery imagery ability may act as a potential buffer against the effects of negative images.